PTH-044 The National Endoscopy Database (NED) Project. (17th August 2016) - Lee, TJW; Macdougall, L; Broughton, R; Rogers, P; Rutter, M
Abstract : Introduction: The UK National Endoscopy Database (NED) Project will enable prospective automatic data collection from endoscopy reporting systems in individual hospitals to a national database. Comprehensive national endoscopy data is vital for quality assurance, benchmarking, audit and research. Once fully deployed NED will accept 1 million procedures per year from over 300 hospitals. Methods: The National Endoscopy Database is based on the successful JAG Endoscopy Training System (JETS). It has been developed to gather data for calculation of key performance indicators (KPIs) for OGD, flexible sigmoidoscopy, colonoscopy and ERCP. All the major endoscopy reporting system (ERS) manufacturers have engaged with the project and are modifying their systems to allow a mandatory minimum dataset to be automatically uploaded to a central database. The new data schema terms are based on MST 3.0 allowing mapping to a standardised terminology. Results: Testing of the upload methodology has demonstrated it is secure, robust, scalable and accurate. To date, two of the major ERS manufacturers have implemented NED compatible software at designated pilot sites. Pilot testing is ongoing. Further roll out and pilot testing is planned over forthcoming months. Conclusion: Initial results from the NED project demonstrate that the proposed upload methodology is reliable and accurate. Modifications to existing ERS are currently being performed by all major manufacturers and testing of uploading real time clinical data underway. The ability to centrally collect endoscopy performance data will be an invaluable tool for monitoring and improving endoscopy quality and will provide a platform for endoscopy research. Disclosure of Interest: None Declared